The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1021/ja961519r
|View full text |Cite
|
Sign up to set email alerts
|

Protioacyl Dications:  Hydrogen/Deuterium Exchange, Rearrangements, and Theoretical Studies1

Abstract: Hydrogen/deuterium exchange was observed by 2H-NMR spectroscopy at the CH3 groups of the long-lived alkanoyl cations CH3CH2CO+ (4), (CH3)2CHCO+ (8), and (CH3)3CCO+ (13) when treated with excess DF·SbF5 superacid. The intermediacy of the corresponding protio(deuterio)acylium dications is suggested to account for the exchanges. Under similar conditions, no exchange was observed in the acetyl ion CH3CO+ (1) in DF·SbF5, but at the same time its electrophilic reactivity is greatly enhanced in superacids. The acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
(25 reference statements)
3
21
0
Order By: Relevance
“…As we have shown earlier [4,5], the rearrangement of pivalaldehyde to methyl isopropyl ketone is strictly dependent on the acidity of the medium. Since pivalaldehyde and pivaloyl cation differ only by a hydride ion, it was worthwhile studying by theoretical methods the nature and reactivity of the pivaloyl ion under superacidic conditions as well as in the presence of hydride donors.…”
supporting
confidence: 53%
See 3 more Smart Citations
“…As we have shown earlier [4,5], the rearrangement of pivalaldehyde to methyl isopropyl ketone is strictly dependent on the acidity of the medium. Since pivalaldehyde and pivaloyl cation differ only by a hydride ion, it was worthwhile studying by theoretical methods the nature and reactivity of the pivaloyl ion under superacidic conditions as well as in the presence of hydride donors.…”
supporting
confidence: 53%
“…Also the acylium salts in superacid media are found to be excellent acylating agents for deactivated aromatics. However, Olah et al have shown that such reactions do not take place with acylium salts themselves in the absence of superacids in aprotic solvents such as SO 2 , SO 2 ClF, AsF 3 , or CH 2 Cl 2 [3].As we have shown earlier [4,5], the rearrangement of pivalaldehyde to methyl isopropyl ketone is strictly dependent on the acidity of the medium. Since pivalaldehyde and pivaloyl cation differ only by a hydride ion, it was worthwhile studying by theoretical methods the nature and reactivity of the pivaloyl ion under superacidic conditions as well as in the presence of hydride donors.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…, with various counterions such as SbF 6 Ϫ , BF 4 Ϫ , SbCl 6 Ϫ , and PF 6 Ϫ are excellent alkylating agents for nucleophiles containing heteroatoms such as N, O, or S. In general they are not capable of C-alkylation of aromatic or aliphatic compounds. In conjunction with protic superacid FSO 3 H:SbF 5 (Magic Acid), however, they were found to alkylate aromatics (1).…”
mentioning
confidence: 99%